Anxiety is associated with higher blood pressure rise induced by cuff inflation. Issue 3 (31st January 2022) - Xie, Feng; Wu, Yanqing; Liu, Huan; Yu, Zuozhong; Xu, Jinsong; Su, Hai
Abstract : Subjects: To assess whether anxiety is associated with a higher rise of blood pressure induced by cuff inflation. Methods: At first, intro-aortic blood pressure was continuously record before cuff inflation as baseline value in 234 patients underwent coronary angiography, then the cuff was inflated to 200 mmHg and the intro-aortic blood pressure was record again as cuff inflation blood pressure. According to anxiety score, the patients were divided into anxiety group, subanxiety group, and nonanxiety group. The difference between the baseline blood pressure and the cuff inflation blood pressure was calculated as cuff inflation-induced blood pressure elevation. When the difference ≥10 mmHg, cuff inflation-induced blood pressure elevation was diagnosed. Results: The cuff inflation systolic blood pressure (134.9 ± 22.4 versus 131.6 ± 22.3  mmHg, P < 0.01) and diastolic blood pressure (80.5 ± 11.9 versus 78.4 ± 11.6 mmHg, P < 0.01) were significantly higher than the baseline values, thus the mean cuff inflation-induced blood pressure elevation on systolic blood pressure was 3.3 ± 4.7 mmHg and that on diastolic blood pressure was 2.1 ± 4.9 mmHg. The anxiety subgroup had significantly higher percentage increase-systolic blood pressure and percentage increase-diastolic blood pressure levels (4.5 ± 3.1% and 5.6 ± 6.3%) than the nonanxiety subgroup (1.9 ± 3.3% and 2.0 ± 6.5%), meanwhile these values in the subanxiety subgroup were higher (3.2 ± 4.1% and 3.4 ± 5.7%) than the nonanxiety subgroup. Conclusion : Cuff inflation can induce a transient rise of intro-aortic blood pressure. Anxiety is associated with higher cuff inflation-induced blood pressure elevation.